Scale Validation of Self-Regulated Learning - Rusdi, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Students' ability to manage themselves during the learning process is essential for development. This research examines student behavior in completing academic assignments due to a lack of discipline and self-control in regulating their learning activities. This research is crucial for developing students' self-management skills in relation to the learning process. The purpose of this study is to develop a scale self-regulated learning with psychometric tests. This research uses a model confirmatory factor analysis (CFA) with the program. AMOS is done because the scale items are built from existing constructs, namely from self-regulated learning Zimmerman's Social Cognition. Therefore, CFA was done because the items were prepared to be used in the Indonesian context, so the scale's validity needed to be tested. Scale development self-regulated learning. This research is concerned with students' ability to prepare themselves for learning. The subjects of this study were 70 students from Makassar State University. The final selection results of the scale consisted of 21 items and loading factor ≥ 0.5 with good reliability, namely AVE = 0.753 (more than 0.50) and composite reliability = 0.955 (more than 0.70).